Strategi Komunikasi Pemasaran Melalui Instagram : Studi Deskriptif Instagram @goalsbeautybar.id - Murtiadi, Murtiadi; Kresyanto, Nadhifah Rara Puspita; Paksi , Yudha Febri Al (Prisani Cendekia Institute, 2023)
Marketing communication activities are efforts to communicate the company, products and services to external parties, including customers, suppliers and business partners. This study aims to describe Goalsbeautybar.id's marketing communication strategy carried out through Instagram social media. This type of research is a descriptive research with a qualitative approach. The subject of this research is the owner of goalsbeautybar.id where the informant has the authority to determine marketing communication strategies through Instagram social media. This data collection technique by observing, interviewing and documentation. Processing methods and data analysis were carried out at the same time during the research process. The process of data analysis in this study the authors use primary data and secondary data. The results of the study show that goalsbeautybar.id carries out a marketing communication strategy by utilizing Instagram social media to introduce their business, influence consumers and increase sales by implementing five components in conducting marketing communications.